2022
DOI: 10.3390/ijms23105596
|View full text |Cite
|
Sign up to set email alerts
|

Chemogenetic Depletion of Hypophysiotropic GnRH Neurons Does Not Affect Fertility in Mature Female Zebrafish

Abstract: The hypophysiotropic gonadotropin-releasing hormone (GnRH) and its neurons are crucial for vertebrate reproduction, primarily in regulating luteinizing hormone (LH) secretion and ovulation. However, in zebrafish, which lack GnRH1, and instead possess GnRH3 as the hypophysiotropic form, GnRH3 gene knockout did not affect reproduction. However, early-stage ablation of all GnRH3 neurons causes infertility in females, implicating GnRH3 neurons, rather than GnRH3 peptides in female reproduction. To determine the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…Our results indicate that while fish gonadotrophs were segregated into two different populations and placed under the control of two distinct neuropeptides during evolution, a common hypothalamic pathway gates the secretion of both gonadotropins. Interestingly, in contrast to GnRH, the novel CCK regulation identified under the current study has a more substantial effect on the gonadotrophic axis, as revealed in our mutants, while the disruption of GnRH and its receptors didn’t lead to any drastic effect on reproduction ( 24, 40 ).…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Our results indicate that while fish gonadotrophs were segregated into two different populations and placed under the control of two distinct neuropeptides during evolution, a common hypothalamic pathway gates the secretion of both gonadotropins. Interestingly, in contrast to GnRH, the novel CCK regulation identified under the current study has a more substantial effect on the gonadotrophic axis, as revealed in our mutants, while the disruption of GnRH and its receptors didn’t lead to any drastic effect on reproduction ( 24, 40 ).…”
Section: Discussionmentioning
confidence: 48%
“…The stimulus was applied manually as a pulse of 300 μl of 30 μg/μl peptide during the first 30 seconds of the imaging session. Hormones were measured in the fractions before and after stimulation using ELISA developed for common carp, which was established in the Levavi-Sivan lab using recombinant carp gonadotropins produced in yeast, and had been previously shown to be suitable for zebrafish (24). Tissue viability was validated by monitoring the morphology and activity of the cells, looking at granulation and calcium changes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore a multitude of hypothalamic neurons, including those that produce the fish Gnrh and Kiss peptides, terminate near, or directly innervate, the distinct gonadotroph cells releasing Lh or Fsh (9), thus conferring control over them without a tetrapodlike median eminence-portal blood system. In zebrafish, Gnrh2/Gnrh3 single or double mutants (10,11) and those with chemogenic depletion of Gnrh3 are fertile (12). Medaka harboring mutations in gnrh1 have well-developed ovaries but fail to ovulate.…”
Section: Introductionmentioning
confidence: 99%